Effect of nanoparticles on the photophysicochemical behaviour of metallophthalocyanines - Moeno, Sharon Keitumetse Gail Mpheletso (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
The synthesis, spectroscopic characterization, and studies of the photophysicochemical behaviour of selective anionic, cationic and neutral metallophthallocyanine (MPc) complexes were carried out and the results are presented herein. Studies on the effect of the central metal ion, the solvent used and the presence of nanoparticles on the photophysicochemical properties were conducted. The findings showed that the photophysicochemical parameters were mostly enhanced in the presence of central metal ions of high atomic numbers and also in the presence of nanoparticles. It was also observed that solvents that encouraged the monomericity of the MPc complexes also lead to improved photophysical and photochemical behaviour. CdTe quantum dots (QDs) stabilized with mercaptocarbonic acids were also observed to cause stimulated emission of the MPcs through Förster resonance energy transfer (FRET) thus acting as energy donors while the respective MPc acted as energy acceptors in all the FRET studies. FRET was observed following the photoexcitation of QDs for all monomeric anionic MPcs but it was also shown to occur for some cationic MPcs in organic media. Both the substituent and solvent used were found to exert a strong influence on the occurrence of FRET. Other cationic MPcs however showed different behaviour in the presence of the meraptocarbonic stabilized CdTe QDs; with the cationic porphyrazine giving clear indications of Pc ring reduction. The rest of the cationic MPcs did not give clear evidence of Pc ring reduction, instead they showed signs of aggregate formation possibly from the assembly of electrostatic ion pair complexes which could result in reduction of the quaternized pyridinium ring of the substituent. Both the QDs and the MPc complex emission spectra were significantly quenched for each in the presence of the other. Stern-Volmer quenching studies indicated that both static and dynamic quenching of the QDs in the presence of MPcs took place. The fluorescence lifetimes of the mercaptopropionic acid (MPA) capped CdTe QDs in the presence of various MPc complexes showed quenching of mostly the longer lifetimes of the QDs in the presence of MPcs suggesting that the surface defects and states are involved in the interaction of the QDs and MPcs. An MPc complex terminating in thio tethers was employed in the conjugation to AuNPs. Spectroscopic and microscopic studies confirmed the formation of the MPc-AuNP conjugate which was also shown to exhibit improved photophysicochemical properties compared to the free MPc.
Keywords: Phthalocyanines; Nanoparticles; Photochemistry; Quantum dots